2006 IEEE/WIC/ACM International Conference on Web Intelligence (WI 2006 Main Conference Proceedings)(WI'06) 2006
DOI: 10.1109/wi.2006.23
|View full text |Cite
|
Sign up to set email alerts
|

A Persistent Labeling Scheme for Dynamic Ordered XML Trees

Abstract: XML is becoming the new standard for the exchange and publishing of data over the Internet. Documents obeying the XML standard can be viewed as trees basically the parse tree of the document. XML database systems often give each item in the document (node in the tree) a unique logical identifier (called a label) and use those labels for an efficient processing of queries, in particular queries involving structural conditions or testing for changes in the document content.Therefore several path indexing and num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…It is easy to determine the relationship between nodes by checking whether one label contains another [28,16,12]. For instance, nodes may be labeled with a number range expressed as two numbers.…”
Section: Nested Set Modelmentioning
confidence: 99%
“…It is easy to determine the relationship between nodes by checking whether one label contains another [28,16,12]. For instance, nodes may be labeled with a number range expressed as two numbers.…”
Section: Nested Set Modelmentioning
confidence: 99%
“…For example, the positional identifier aaaaabcbcbcdddde would be rewritten as 5a3(bc)4de. In [12] a labelling scheme very similar to LSDX is proposed and differs only in the method to determine the positional identifier of a node. However, LSDX and the two labelling schemes derived from it do not always produce unique node labels for several corner-case update scenarios and therefore they are unsuitable for use as dynamic labelling schemes for XML.…”
Section: Prefix Schemesmentioning
confidence: 99%
“…However, the factorization is still quite expensive. In [18], it was reported that the ORDPATH method [17] achieves both better structural information extraction and storage consumption than the existing prefix-based labeling methods such as LSDX [8] and persistent labeling schemes [9,12]. Other two update-friendly labeling schemes, namely QED [14] and CDBS [15], are more efficient than the ORDPATH method in respect to data updates.…”
Section: Related Workmentioning
confidence: 99%
“…ORDPATH, which is implemented in Microsoft R SQL Server T M 2005, is also an update-friendly labeling method based on the DO number. [18] reported that ORDPATH achieves both better structural information extraction and storage consumption than the existing prefix-based labeling methods such as LSDX [8] and persistent labeling schemes [9,12]. DO-VLEI achieves efficient structural information extraction as ORDPATH does.…”
Section: Introductionmentioning
confidence: 99%